2020
DOI: 10.1002/art.41481
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Open Label Study of Anakinra in Intravenous Immunoglobulin–Resistant Kawasaki Disease

Abstract: Objective. Anakinra has been shown to be successful in preventing and treating cardiovascular lesions both in experimental murine models of Kawasaki disease (KD) and in several studies of intravenous immunoglobulin (IVIG)and steroid-resistant patients with KD. This study was undertaken to determine the safety of blocking interleukin-1 in patients with IVIG-resistant KD. Methods. Sixteen patients were included in the present study. Patients with KD who were not responsive to 1 or more courses of 2 mg/kg of IVIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 64 publications
(92 reference statements)
5
44
0
3
Order By: Relevance
“…Anakinra has a good safety profile even in case of acute infection (64)(65)(66). In IVIG-resistant KD, it was without major adverse events, and it showed clinical efficiency by reducing fever, as well as biological efficiency in lowering markers of inflammation, and echocardiographic features like coronary artery dilatation (67). As an extrapolation to IVIG resistant KD, anakinra has been used in PIMS (14,16,21,27,28).…”
Section: Anakinramentioning
confidence: 99%
“…Anakinra has a good safety profile even in case of acute infection (64)(65)(66). In IVIG-resistant KD, it was without major adverse events, and it showed clinical efficiency by reducing fever, as well as biological efficiency in lowering markers of inflammation, and echocardiographic features like coronary artery dilatation (67). As an extrapolation to IVIG resistant KD, anakinra has been used in PIMS (14,16,21,27,28).…”
Section: Anakinramentioning
confidence: 99%
“…Daily ANA treatment was continued for a maximum of 15 days and the median duration of treatment was 15 days (10 patients). 25 ANA resulted effective in controlling fever and disease activity and reduced inflammatory markers, indeed 87.5% of patients in the per-protocol group became afebrile within 48 h, a reduction of disease activity by 50% was reached by 93.3% of children with KD of physician’s evaluations and by 100% of parent’s evaluations and CRP values were normalized at day 30 from disease onset (13 of 16). In addition, ANA seems effective in both treating and preventing coronary involvement, since 10 patients (62.5%) evidenced a coronary z score >2.5 at the initial screening visit with decreased <2.5 in 5 patients (31%) at the end of therapy.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, ANA seems effective in both treating and preventing coronary involvement, since 10 patients (62.5%) evidenced a coronary z score >2.5 at the initial screening visit with decreased <2.5 in 5 patients (31%) at the end of therapy. 25 It also showed good safety and tolerability profiles with primarily reported nonserious adverse events and no opportunistic infections. 25 …”
Section: Discussionmentioning
confidence: 98%
“…A recently published phase II open-label study supported the use of anakinra in patients with IVIG-resistant Kawasaki disease. The authors reported the safety of this drug and its effectiveness in reducing fever, inflammatory markers and coronary artery dilations in patients refractory to at least one dose of IVIG (31). Since anakinra is a promising treatment in this group of patients, it may be considered even in patients with MIS-C with severe cardiological involvement or if lack of response to IVIG and glucocorticoids occurs.…”
Section: Discussionmentioning
confidence: 99%